2013
DOI: 10.1152/ajpheart.00878.2012
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast KATP currents modulate myocyte electrophysiology in infarcted hearts

Abstract: Cardiac metabolism remains altered for an extended period of time after myocardial infarction. Studies have shown fibroblasts from normal hearts express KATP channels in culture. It is unknown whether fibroblasts from infarcted hearts express KATP channels and whether these channels contribute to scar and border zone electrophysiology. KATP channel subunit expression levels were determined in fibroblasts isolated from normal hearts (Fb), and scar (sMI-Fb) and remote (rMI-Fb) regions of left anterior descending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Targeting ventricular fibroblast ion currents to produce antiarrhythmic electrophysiological changes in and around the infarct site may provide a new paradigm for the management of complex ventricular arrhythmias (43). Evidence suggests that modulating the fibroblast ATP-regulated K þ current may be exploited to alter border-zone electrophysiology in infarcted hearts (44).…”
Section: Novelty and Potential Importancementioning
confidence: 99%
“…Targeting ventricular fibroblast ion currents to produce antiarrhythmic electrophysiological changes in and around the infarct site may provide a new paradigm for the management of complex ventricular arrhythmias (43). Evidence suggests that modulating the fibroblast ATP-regulated K þ current may be exploited to alter border-zone electrophysiology in infarcted hearts (44).…”
Section: Novelty and Potential Importancementioning
confidence: 99%
“…5 infarcted heart model, pinacidil treatment increased whole-cell K ATP current which was blocked by glibenclamide (Benamer et al, 2013). It is thought that activation of fibroblast K ATP current would reduce the depolarizing effect on cardiomyocytes, which would subsequently prevent early after depolarisations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although K ATP channel subunits are abundant in cardiomyocytes, Benamer et al (2009Benamer et al ( , 2013 reported mRNA and protein expression of SUR2 and Kir6.1 as the two most prominently expressed subunits in mouse and rat ventricular fibroblasts (Benamer et al, 2013(Benamer et al, , 2009). Subsequently, they recorded current carried by the Kir6.1/SUR2 channel complex, which was shown to be sensitive to both pinacidil and glibenclamide.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Of note, cardiac K ATP channels are also present and active in fibroblasts, suggesting that one must consider cardiac pre-/post-conditioning effects on cells other than just cardiomyocytes. 6870 As with other K + channels, K ATP opening favours re-/hyperpolarization. While beneficial in preventing spurious excitation of resting cells, this also shortens the action potential (AP) duration (APD) and reduces the refractory period.…”
Section: Introduction To Cardiac Mechano-sensitivitymentioning
confidence: 99%